Oral administration of dopamine boosts anti-Vibrio immunity in shrimp through Dorsal pathway activation - Zi-ang Wang; Shun Liu; Zexu Zhao; Xiaojia Liao; Linwei Yang; Hongliang Zuo; Shaoping Weng; Jianguo He; Xiaopeng Xu (Fish & Shellfish Immunology, 2026)

Numerical modelling of masonry arch bridges: Classical strategies and emerging approaches - Nicola Grillanda; Stanyslav Grosman; Laura Niero; Linwei He; Imrose B. Muhit (Engineering Structures, 2026)

SAF-YOLO: Super-resolution augmented detection model with visual state space enhancement for safflower filament picking - Duan Mengyu; Wang Xiaorong; Qiu Linwei; Li Menghao; Chen Jinrong; He Liang (Precision Agriculture, 2026)

Heteroaptamer recognition mediated strand displacement amplification for efficient electrochemical analysis of beta-2-microglobulin in breast milk - Yaqin Tang; Tingting He; Linwei Pan; Yanni Wang; Xiaolong Li; Xia Zhao; Daxiu Li; Baoting Dou (Food Chemistry, 2026)

Digital design optimization and off-site modularization for modern stone masonry construction - Jian Zhang; Kavinda Isuru Nanayakkara; Linwei He; Helen Fairclough; Andrew Liew; Colin Smith; Matthew Gilbert (Engineering Structures, 2026)

The influences of China's Cultivated Land Fertility Protection Subsidy policy on farmers' agro-eco-environmental protection behavior: an application of the extended theory of planned behavior - Ting Liu; Linwei Du; Jiaona Hou; Xiancheng Zeng; Wenyan Zhang; He Xu (Journal of Environmental Management, 2025)

Identification of the exposure pathway to micro-scaled biogenic silica debris via diet and its potential effect in promoting esophageal squamous cell carcinoma - Shenxi Deng; Yi Yang; Erica Celeste Conway; Si Li; Cha Huang; Zigu Chen; Haisheng Wu; Yuan He; Shuzhe Xie; Aifang Ji; Jingyan Zhang; Yansheng Gu; et al. (Journal of Hazardous Materials, 2025)

A cytokine receptor domeless restrains mud crab reovirus infection via JAK-STAT signaling pathway in mud crab (Scylla paramamosain) - Hengwei Deng; Yetong Ke; Shaoping Weng; Lei Hu; Wenfeng Zhang; Yujia Sun; Linwei Yang; Xuewen Wang; Mingyang Feng; Weiliang Guo; Zhihong Zhong; Dongdong Zhang; et al. (Fish & Shellfish Immunology, 2025)

Minimum material vault designs generated via adaptive layout optimization - Linwei He; Helen E. Fairclough; Matthew Gilbert; Andrew Liew; Karol Bołbotowski (Engineering Structures, 2025)

Concurrent optimization of truss structures and build directions for multi-axis additive manufacturing - Jun Ye; Xiaoyang Lin; Hongjia Lu; Linwei He; Guan Quan; Cheng Huang; Paul Shepherd (Engineering Structures, 2025)

Recent Research Advances on the Hippo‐Yki Pathway of Crustaceans: Current Knowledge and Potential Applications in Crustacean Aquaculture - Linwei Yang; Yushi Gan; Hengwei Deng; Jianguo He; Xiaopeng Xu (Reviews in Aquaculture, 2025)
The Hippo‐YAP/Yki pathway is critical for the regulation of physiological responses in various biological processes from invertebrates to mammals. Crustaceans, in particular shrimp and crabs, are important food sources worldwide. In response to the needs of crustacean aquaculture and disease control, the regulatory mechanisms of crustacean life activities, especially immunity, have been increasingly emphasized. Emerging clues suggest that Hippo‐Yki pathway is important for immunity and regeneration in crustaceans. In this review, the structure, activation pattern, response mechanism to pathogen invasion, and crosstalk with other signaling cascades of the Hippo‐Yki pathway in aquaculture crustaceans are summarized and its similarities and differences with those in mammals and Drosophila are investigated. Based on this, the roles of the Hippo‐Yki pathway in crustacean immune response and limb regeneration are further discussed, and the application potential of strategies pharmacologically or biologically targeting this pathway for crustacean disease control and breeding is theoretically explored.

A novel perlucin with immune regulatory functions protects Litopenaeus vannamei against Vibrio parahaemolyticus infection - Zi-ang Wang; Linwei Yang; Zexu Zhao; Shaoping Weng; Jianguo He; Xiaopeng Xu (Fish & Shellfish Immunology, 2024)

Two cytokine receptor family B (CRFB) members in orange-spotted grouper Epinephelus coioides, EcCRFB3 and EcCRFB4, negatively regulate interferon immune responses to assist nervous necrosis virus replication - Siyou Huang; Yiling Kang; Rui Zheng; Linwei Yang; Jie Gao; Wanting Tang; Jing Jiang; Jianguo He; Junfeng Xie (Fish & Shellfish Immunology, 2024)

Orange-spotted grouper IFNh response to NNV or MSRV and its potential antiviral activities - Siyou Huang; Rui Zheng; Yiling Kang; Linwei Yang; Jie Gao; Qingqing Liu; Shaoping Weng; Jianguo He; Junfeng Xie (Fish & Shellfish Immunology, 2024)

Basigin binds bacteria and activates Dorsal signaling to promote antibacterial defense in Penaeus vannamei - Linwei Yang; Zi-ang Wang; Yushi Gan; Hongliang Zuo; Hengwei Deng; Shaoping Weng; Jianguo He; Xiaopeng Xu (Fish & Shellfish Immunology, 2023)

The Hippo-Yki pathway downstream transcription factor Scalloped negatively regulates immune defense against Vibrio parahaemolyticus infection in shrimp - Linwei Yang; Deyu Han; Zi-ang Wang; Nuo Chen; Hongliang Zuo; Zhixun Guo; Menghuang Xu; Shaoping Weng; Jianguo He; Xiaopeng Xu (Fish & Shellfish Immunology, 2023)

Iron phthalocyanine decorated porous biomass-derived carbon as highly effective electrocatalyst for oxygen reduction reaction - Linwei Zhang; Xudong Jiao; Guangjing He; Zhaodi Shen; Wei Wang (Journal of Environmental Chemical Engineering, 2023)

A novel Toll receptor from Pacific white shrimp Penaeus vannamei is involved in immune defense against Vibrio parahaemolyticus infection - Shengwen Niu; Yuening Zhu; Ran Geng; Nuo Chen; Mengting Luo; Hongliang Zuo; Linwei Yang; Shaoping Weng; Jianguo He; Xiaopeng Xu (Aquaculture, 2023)

A novel chitinase Chi6 with immunosuppressive activity promotes white spot syndrome virus (WSSV) infection in Penaeus vannamei - Shengwen Niu; Yuening Zhu; Ran Geng; Mengting Luo; Hongliang Zuo; Linwei Yang; Shaoping Weng; Jianguo He; Xiaopeng Xu (Fish & Shellfish Immunology, 2023)

Responses of the functional structure of soil microbial community to livestock grazing in the T ibetan alpine grassland - Yunfeng Yang; Linwei Wu; Qiaoyan Lin; Mengting Yuan; Depeng Xu; Hao Yu; Yigang Hu; Jichuang Duan; Xiangzhen Li; Zhili He; Kai Xue; Joy van Nostrand; et al. (Global Change Biology, 2013)
Microbes play key roles in various biogeochemical processes, including carbon (C) and nitrogen (N) cycling. However, changes of microbial community at the functional gene level by livestock grazing, which is a global land‐use activity, remain unclear. Here we use a functional gene array, GeoChip 4.0, to examine the effects of free livestock grazing on the microbial community at an experimental site of T ibet, a region known to be very sensitive to anthropogenic perturbation and global warming. Our results showed that grazing changed microbial community functional structure, in addition to aboveground vegetation and soil geochemical properties. Further statistical tests showed that microbial community functional structures were closely correlated with environmental variables, and variations in microbial community functional structures were mainly controlled by aboveground vegetation, soil C/N ratio, and NH 4 + ‐N . In‐depth examination of N cycling genes showed that abundances of N mineralization and nitrification genes were increased at grazed sites, but denitrification and N‐reduction genes were decreased, suggesting that functional potentials of relevant bioprocesses were changed. Meanwhile, abundances of genes involved in methane cycling, C fixation, and degradation were decreased, which might be caused by vegetation removal and hence decrease in litter accumulation at grazed sites. In contrast, abundances of virulence, stress, and antibiotics resistance genes were increased because of the presence of livestock. In conclusion, these results indicated that soil microbial community functional structure was very sensitive to the impact of livestock grazing and revealed microbial functional potentials in regulating soil N and C cycling, supporting the necessity to include microbial components in evaluating the consequence of land‐use and/or climate changes.